TYPES OF GYNECOLOGICAL INFLAMMATORY DISEASES (Modern education and development, 2025)
Inflammatory diseases of women are one of the most common gynecological diseases. The anatomical and physiological characteristics of the female body play a special role in their high incidence. These include the proximity of the genitals to external influences, cyclical changes in each month associated with menstrual function, as well as traumatization of the genital tract tissue to a greater or lesser extent during abortion and childbirth.